Physical activity of adolescents in health and recreation facilities: motives and interests - Бондар, Тарас; Головійчук, Ірина (Slobozhanskyi Herald of Science and Sport, 2019)
Taras Bondar & Iryna Holoviichuk Purpose: elucidation of the motives and interests of adolescents regarding forms of physical activity in health and recreation facilities. Material & Methods: in a sociological study, adolescents aged 10–15 years participated in children's health and recreation facilities. Results: in the process of analyzing the survey data, it was found that for adolescent boys, regardless of age, in the exercise and sports, the existence of certain rules and boundaries is very important, which affects their interest and motivation. For girls, on the contrary, the existence of rules and boundaries is a factor that reduces the interest in physical exercises. The presence of emotional coloring and a variety of motor modes, on the contrary, stimulate girls' creativity and imagination, which leads to their enjoyment of motor activity. Conclusions: in the process of analyzing the survey data, the diversity and non-standard interests of adolescents in physical education and sports and the gender characteristics of their motivation were established. The identified need for the development of organizational and managerial technologies that will take into account the interests and motives of adolescents, with the aim of their active involvement in motor activity.